TRADISI JUMAT KLIWONAN SEBAGAI KEARIFAN LOKAL MASYARAKAT NELAYAN DI KABUPATEN CILACAP, JAWA TENGAH - Bagus Wiranto (Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
This article describes Friday Kliwonan tradition in fishermen community in Cilacap Regency which is acculturation from some practice in the past and still trusted and done until today. This is related to how the ritual is performed and the meaning of the ritual, the ban on sea fishing on Friday Kliwon, and other activities on that day. In addition, the article on this tradition also explains the meaning of this relationship between tradition of this Friday Kliwonan as a local wisdom of Cilacap Regency fishermen community viewed from the spiritual side of society, social relations of society, and the ecological side.